Characteristics and efficacy of cytosine and cytidine deaminase - Qusay Chalabi; Zahraa Hammodat (College of Education for Pure Sciences, 2007)
Abstract The study concerned with determination of some properties of cytosine deaminase activity in serum and erythrocytes haemolysate in normal human individuals, by spectral method. The study also included the determination of optimum conditions for enzyme activity and the normal values of specific enzyme activity. It included also, measuring the values of specific enzyme activity for cases of serum patients covering: patients with Leukemia Diabetes, and Thalassemia. Moreover, the present study determined the specific activity of cytidine deaminase in serum and erythrocytes haemolysate using the same optimum conditions for cytosine deaminase in normal individuals and cases of Diabetes . The result of the study showed that maximum activity of cytosine deaminase in serum and erythrocytes hemolysate was obtained using (250 µM) and (150 µM) of buffer solution (Tris-HCl) for serum and erythrocytes respectively at pH(7.5) and (3 µM) cytosine as a substrate as well as (100 µL) and (50 µL) for serum and erythrocytes respectively as a source of enzyme for (2 min.) at (30 ºC) . The results of the study also showed that the enzyme was active towards the substrate 5-Methyl cytosine, while in active towards Deoxy cytidine mono phosphate and cytidine triphophate. Also the presence of some metal salts such as MgCl2, CoCl2, HgCl2, KCl, CuCl2 in the reaction solution led to inhibited of the enzyme inhibited the activity. The analysis also indicated the non-existence of any significant difference of values of cytosine deaminase activity in Diabetic, Leukemia and normal individuals. However, the enzyme activity was higher in Thalassemia patients by (1.5) folds than in normal cases. Finally, the statistical results of cytidine deaminase showed that a significant difference between normal and Diabetes.